PERTANGGUNGJAWABAN KORPORASI TERHADAP PELANGGARAN ILLEGAL, UNREPORTED, UNREGULATED FISHING (IUU FISHING) - Turfatul Atiyah (Dinamika, 2021)
ABSTRACT Laws and regulations in Indonesia already exist that regulate the protection of personal data, but it is still not specifically set specifically. Formulation of the problem namely: How is the legal protection of one's personal rights in the social media according to Act Number 19 of 2016 concerning Information and Electronic Transactions? What legal remedies can be taken by victims whose personal data is distributed without permission? How is the modus operandi of spreading one's personal data on social media? Using the type of normative juridical research (Normative Legal Research), namely research conducted based on regulations and sources of applicable legal materials. Legal protection given to personal data is preventive and repressive where both regulate both the contents of the criminal sanction article. Legal remedies provided in the form of ordinary and extraordinary legal efforts. With some of the mechanisms that occur in the abuse, additional system strengthening is needed so that it is not easily accessed illegally.Keywords: Personal Data, Legal Protection, Social Media ABSTRAKPeraturan perundang-undangan di Indonesia sudah ada yang mengatur mengenai perlindungan data pribadi, namun masih belum spesifik mengatur secara khusus. Rumusan masalah yaitu : Bagaimana perlindungan hukum terhadap hak pribadi seseorang dimedia sosial menurut Undang-Undang Nomor 19 Tahun 2016 tentang Informasi dan Transaksi Elektronik ? Apa upaya hukum yang dapat ditempuh oleh korban yang data pribadinya disebarkan tanpa izin ? Bagaimana modus operandi penyebaran data pribadi seseorang dimedia sosial ?. Menggunakan jenis penelitian yuridis normatif (Normatif Legal Research) yaitu penelitian yang dilakukan berdasarkan peraturan dan sumber-sumber bahan hukum yang berlaku. Perlindungan hukum yang diberikan terhadap data pribadi adalah secara preventif dan represif dimana kedua-duanya mengatur baik tentang isi pasal sanksi pidananya. Upaya hukum yang diberikan berupa upaya hukum biasa dan luar biasa. Dengan beberapa mekanisme yang terjadi dalam tindakan penyalahgunaan tersebut perlu tambahan penguatan sistem agar tidak mudah diakses secara ilegal.Kata Kunci : Pertanggungjawaban Korporasi, Pelanggaran, IUU Fishing